Effectiveness and Safety of Cryoablation in Patients With Atrial Fibrillation Episodes of <24 h Duration: A Propensity-Matched Analysis - Jiang, Chunying; Zhao, Dongdong; Tang, Kai; Wang, Yiqian; Li, Xiang; Jia, Peng; Xu, Yawei; Han, Bing (Frontiers in Cardiovascular Medicine, 2021)
Background: Paroxysmal atrial fibrillation (AF) is closely related to pathophysiologic processes and clinical outcomes. However, it is uncertain whether cryoablation of pulmonary veins isolation is effective and safe for patients with symptomatic and drug refractory AF episodes of <24-h duration. Methods: The patients were designed into Group A (253 patients with paroxysmal AF episodes of <24-h duration) and Group B (253 patients with paroxysmal AF lasting for 24 h or longer) on a 1:1 basis by identical propensity scores. Mortality, stroke/transient ischemic attack (TIA), and complications relevant to the cryoablation procedure were compared, and recurrence of atrial tachyarrhythmia was analyzed for clinical independent predictors. Results: The rate of atrial tachyarrhythmia recurrence was 21.74% in Group A and 30.04% in Group B, respectively (P = 0.042). At 12-month follow-up from the procedure, lower incidences of stroke/TIA endpoint of the patients were observed in Group A compared with Group B by Kaplan–Meier analysis [HR 0.34 (0.13–0.87), P = 0.025]. No significant differences in mortality and complications relevant to the cryoablation procedure were observed between Group A and Group B. Moreover, adjusted multivariable Cox regression analysis showed that <24-h paroxysmal AF type (HR 0.644, 95% CI: 0.455–0.913, P = 0.014) and left atrium diameter (LAD) (>40 mm) (HR 1.696, 95% CI: 1.046–2.750, P = 0.032) were independently associated with the incidence of recurrence of atrial tachyarrhythmia in the study. Conclusion: Our findings indicated that <24-h paroxysmal AF type was obviously associated with an increased success rate of cryoablation and reduced incidence of stroke/TIA during the follow-up period. Therefore, there is superior effectiveness and similar safety in patients with AF episodes of <24-h duration compared with patients with longer paroxysmal AF duration.